2019
DOI: 10.3389/fonc.2019.01365
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Pre-treated Neutrophil-Lymphocyte Ratio in the Management of Urothelial Carcinoma: A Systemic Review and Meta-Analysis

Abstract: Purpose: We performed a study-level meta-analysis to summarize the current evidence on the correlation between pretreatment neutrophil-to-lymphocyte ratios (NLR) and oncological outcomes in each type of management for urothelial carcinoma. Method: All articles published until February 2017 in PubMed, Scopus, and EMBASE database were collected and reviewed. The current evidence on correlations between pretreatment NLR and oncological outcomes in each type of management for urothelial carcinoma, including transu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…The inflammatory indexes have been widely studied in patients with malignant diseases [ 12 ] and neurodegenerative diseases [ 13 ]. Some studies demonstrated that the inflammatory indexes were associated with other inflammatory indicators, such as IL-6, CRP, and TNF-α, and were useful for predicting disease progression, treatment response, and prognosis [ 12 , 31 ]. These findings imply that the inflammatory indexes may reflect the degree of inflammation in these diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inflammatory indexes have been widely studied in patients with malignant diseases [ 12 ] and neurodegenerative diseases [ 13 ]. Some studies demonstrated that the inflammatory indexes were associated with other inflammatory indicators, such as IL-6, CRP, and TNF-α, and were useful for predicting disease progression, treatment response, and prognosis [ 12 , 31 ]. These findings imply that the inflammatory indexes may reflect the degree of inflammation in these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the discrepancy of these results may be the reporting and publication bias. For example, in a meta-analysis about the correlation of NLR with outcomes of urothelial carcinoma, publication bias could not be excluded by inverted funnel plots [ 12 ]. An analysis of 1915 publications on cancer prognostic markers found that almost all articles reported statistically significant results [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have found NLR to be related to inferior prognosis in various solid tumors. 5,11,12,16,28 A higher NLR value often indicates a higher neutrophil or lower lymphocyte count. Neutrophils can secrete essential factors, including IL-8, VEGF, and elastase for tumor growth and metastases.…”
Section: Dovepressmentioning
confidence: 99%
“…9,10 Previous studies have presented that NLR could serve as a systemic inflammatory response index to provide important information regarding inflammation and immune state. NLR has been identified as a prognostic biomarker in several cancer types, including urinary tract epithelial tumors, prostate cancer, and non-small cell lung cancer (NSCLC), [11][12][13][14] although the relationship between NLR and long-term outcomes in SCLC remains to be completely understood. Thus, this study was designed to further explore the effects of NLR on the prognosis and identify other factors that modify this association in patients with SCLC.…”
Section: Introductionmentioning
confidence: 99%